Consanguinity Associated with Child and Adult Mortality in 24 Asian and African Countries, an Ecological Study - M Saadat (Tehran University of Medical Sciences, 2007)
Background: Although numerous studies have found deleterious effects of inbreeding on childhood and pre-reproductive mortality, one question remains inadequately addressed: Dose inbreeding lead to increased childhood mortality rates in countries with high level of consanguinity? Methods: To evaluate the public health impact of inbreeding on offspring mortality, the association between mean of inbreeding coefficient (α) and sex specific child and adult mortality rates in 24 countries from Asia and Africa was analyzed. Results: Statistical analysis showed that countries with relatively higher rates of consanguineous marriages have higher mortality rates than the countries with lower consanguinity rates. Also, countries with relatively higher GDP per capita have lower mortality rates. After controlling the GDP per capita, significant positive correlations between α and child (Female: r=0.4355, df=21, P=0.038; Male: r=0.3991, df=21, P=0.059) mortality rates were observed. There was no significant correlation between α and adult (Female: r=0.2977, df=21, P=0.168; Male: r=0.2207, df=21, P=0.312) mortality rates, after controlling for GDP per capita. Conclusion: It is concluded that consanguinity influences child deaths rate independent of the GDP per capita and that a large proportion of deaths could be attributed to inbreeding in several countries due to high frequencies of consanguinity.